The Little Data Book on Gender 2011 - World Bank; World Bank (Washington, D.C. : The World Bank, 2011)
This handy pocket guide is a quick reference for users interested in the gender statistics. The book presents gender-disaggregated data for more than 200 countries in an easy country-by-country reference on demography, education, health, labor force, political participation and the Millennium Development Goals. The book's summary pages cover regional and income group aggregates.
Keywords: Child mortality; Economic opportunities; Family planning; Fertility; Gender; Gender equality; Gender gaps; Labor force; Maternal health; Sex ratio; World Population